Characteristics of Endometriosis Patients in Dr. Mohammad Hoesin General Hospital on 2018 to 2020 - Leriva, Ratu Tenny; Iskandar Zulqarnain; Hadrians Kesuma Putra; Awan Nurtjahyo; Syifa Alkaf (HM Publisher, 2022)
Background. Endometriosis is defined as the presence of endometrial-like tissue outside the uterus. The prevalence of endometriosis is not known with certainty because it is necessary to perform a laparoscopy to confirm the diagnosis of endometriosis and is usually found during examination for other indications. This study aims to explore the characteristics of endometriosis patients at Dr. Mohammad Hoesin General Hospital Palembang. Methods. This research is descriptive observational research. The research data were obtained from the medical records of endometriosis patients treated at Dr. Mohammad Hoesin General Hospital Palembang from 2018 to 2020. Results. Of the 105 sample data studied, the most distribution of endometriosis patients was in the reproductive age group (15-49 years) (99%), menarche 12-14 years (67.6%), the location of endometriosis in the ovaries (58.1%), status indoor workers (99%), marital status (85.7%), fertile (43.8%), and infertile patients (41.9%), the chief complaint of dysmenorrhea (66.7%), stage IV disease (63, 8%), nullipara (60%), surgical management (79%). Conclusion. Most of the characteristics of endometriosis patients were in the reproductive age group (15 – 49 years), menarche 12-14 years, endometriosis location in the ovary, indoor worker status, marital status, infertility, the main complaint of dysmenorrhea, stage IV disease, nullipara, surgical treatment.